ANALISIS PENGARUH ECONOMIC FREEDOM TERHADAP FOREIGN DIRECT INVESTMENT DI NEGARA ASEAN - Ach. Habibi; Wahyu Hidayat R (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2017)
FDI is important for economic development, raising the level of productivity, employment and income of country. The condition of FDI can be affected by location specific factors. One of them is economy The main role in the economy of a country is the government and in economic decision-making process, not the government rarely held hostage by political interests, So the need for evaluation.The purpose of this research is to examine impact of Economic Freedom which consists of trade freedom and tax burden on FDI in ASEAN countries the period 2004-2015. Analysis tool used regression panel data. The results of this research show that trade freedom and tax burden positive statistically in influencing FDI in ASEAN countries. Therefore, the Government is expected to reduce trade barriers andt tax burden to attract the flow of FDI.